Flexible GaN Light‐Emitting Diodes Using GaN Microdisks Epitaxial Laterally Overgrown on Graphene Dots. Issue 35 (27th June 2016) - Chung, Kunook; Yoo, Hyobin; Hyun, Jerome K.; Oh, Hongseok; Tchoe, Youngbin; Lee, Keundong; Baek, Hyeonjun; Kim, Miyoung; Yi, Gyu‐Chul
Abstract : The epitaxial lateral overgrowth (ELOG) of GaN microdisks on graphene microdots and the fabrication of flexible light‐emitting diodes (LEDs) using these microdisks is reported. An ELOG technique with only patterned graphene microdots is used, without any growth mask. The discrete micro‐LED arrays are transferred onto Cu foil by a simple lift‐off technique, which works reliably under various bending conditions.